The phenomenon of extremism in religion in Muslim life: an analysis of its roots, causes and nature - Ushama, Thameem (Canadian Center of Science and Education, 2014)
This paper strives to analyse the roots, causes and nature of extremism in Muslim life from a contemporary Muslim perspective. Its scope is limited to historical, ideational and psychological roots of contemporary extremism among Muslim individuals and organizations, regardless of whether they live as the majority or minority in their country. It employs the qualitative method, focusing on content analysis of the writings of Muslim scholars and observations of extremists as they resort to activities that lead to fanaticism or obsession in their words and deeds. It is hoped this will awaken Muslims from their ignorance and raise their consciousness to know the history to enable them to correct themselves from their flaws or errors should they resort to any extremist tendencies in their intentions, interactions, interpretations, actions, articulations, analyses, speeches, sermons, dialogues, debates and writings or teachings, either consciously or unconsciously, whether in academic or social or political or religious or interfaith discourses. Lastly, it provides a conclusion and recommendations.